Preservation challenges for heritage landscapes during historic-city transformation: Datong Ancient City, China - Wang, Suhua; Zhang, Jing; Mohd Isa, Norliza; Li, Lintong (Cogent OA, 2026)
This paper examines how an investment-driven programme reshaped the heritage landscape of Datong Ancient City, 2008–2024, with a follow-up in February 2025. Guided by the 2021 Call for Action marking the tenth anniversary of the 2011 UNESCO Recommendation on the Historic Urban Landscape, we adapt and localise an existing challenge framework and operationalise it through directed qualitative content analysis and process tracing within a parameterised comparative matrix, in keeping with international conservation principles. We triangulate municipal regulations, contemporaneous media and archives, and structured field observation across nine municipally designated sites: Huayan and Shanhua Temples, the Mosque, Guandi and Confucian Temples, East & West Drum Tower Streets, the City Walls, the Drum Tower and the Palace of Prince Dai. Results are organised under three domains: socioeconomic, political and historical, making development-protection trade-offs visible at site scale. We identify recurrent patterns, including tenant and function homogenisation and a weak night-time economy; approval and coordination frictions and maintenance-display imbalances; and pressures on authenticity and integrity, blurred stratification and commodification. Building on these findings, we propose a policy playbook comprising tenant-retention and chain-store caps, authenticity impact statements and public participation windows, and no-net-loss authenticity covenants, and a lightweight monitoring toolkit with ex-ante risk mapping and ex-post indicators for asset condition, maintenance, tenant mix, signage and participation. The study is a historically bounded case; claims are limited to Datong’s governance context and time window. The lens and tools are offered as transferable heuristics for medium-sized historic cities undertaking timetable-bound capital programmes and tourism-oriented image-making.